2021
DOI: 10.1016/j.amsu.2021.102347
|View full text |Cite
|
Sign up to set email alerts
|

The effect of preoperative sublingual buprenorphine on postoperative pain after lumbar discectomy: A randomized controlled trial

Abstract: Background Lumbar discectomy is one of the most common surgical procedures performed to manage pain caused by the protrusion of an intervertebral disc. Postoperative pain management can be challenging and might lead to increased intake of opioids. Objective : The aim of this study was to determine the effect of preoperative sublingual buprenorphine on severity of pain after lumbar disc surgery and postoperative intake of morphine. Methods This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…However, this change was not seen at 12 or 24 h, p > 0.05. The incidence of adverse effects (nausea, vomiting, and pruritus) was not significantly different between the two groups (P > 0.05) [13].…”
Section: Preoperative Considerationsmentioning
confidence: 79%
“…However, this change was not seen at 12 or 24 h, p > 0.05. The incidence of adverse effects (nausea, vomiting, and pruritus) was not significantly different between the two groups (P > 0.05) [13].…”
Section: Preoperative Considerationsmentioning
confidence: 79%
“…Sublingual buprenorphine was also assessed in the perioperative setting [ 93 ]. Sublingual buprenorphine has a 60-min time to reach the maximum plasma concentration, a 11.2 h half-life, and a 35% bioavailability, and is actually approved for opioid withdrawal, but not for chronic pain management [ 84 ].…”
Section: Current Multi-mechanistic (Mor/nop) Opioidsmentioning
confidence: 99%
“…7 Buprenorphine is an important aid in pain control for patients who are being prescribed this medication and has even been used for postoperative neurosurgical patients for pain control in those without opioid use disorder. 8,9 For patients prescribed buprenorphine, a retrospective cohort suggests that continuing buprenorphine is associated with lower opioid requirements for analgesia: Patients who continued buprenorphine required lower doses of intravenous patient-controlled anesthesia opioids when compared with patients who did not receive buprenorphine on the day after surgery. 10 Further evidence toward buprenorphine aiding in pain control was described in a cohort study of obstetric patients undergoing cesarean section, which found that patients treated with buprenorphine had similar mean opioid requirements to patients treated with methadone, a full opioid agonist.…”
mentioning
confidence: 99%